Moral laboratories : family peril and the struggle for a good life - Mattingly, Cheryl, 1951- (University of California Press, 2014)
Moral Laboratories is an engaging ethnography and a groundbreaking foray into the anthropology of morality. It takes us on a journey into the lives of African American families caring for children with serious chronic medical conditions, and it foregrounds the uncertainty that affects their struggles for a good life. Challenging depictions of moral transformation as possible only in moments of breakdown or in radical breaches from the ordinary, it offers a compelling portrait of the transformative powers embedded in day-to-day existence. From soccer fields to dinner tables, the everyday emerge.